Solemn Processions and Terrifying Violence: Spectacle, Authority, and Citizenship during the Lachine Canal Strike of 1843 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2010)
During the winter of 1843, over one thousand Irish migrant labourers hired to work on the expansion of the Lachine Canal near Montreal struck for higher wages. In the months that followed, they employed a range of public spectacles including nocturnal processions, charivaris, riots, and parades to intimidate their economic rivals and lobby for support from the broader community. These crowd events played a pivotal role in the way that elites were re-conceptualizing the city, citizenship, and their own authority at the dawn of a period that would see Montreal transformed by mass immigration and the entrenchment of a capitalist economy. They also offer some insight into what the city meant to the striking canal workers as an engine of exploitation as well as a site of refuge and resistance.